Relative force and PAP in swimming start performance - Cuenca-Fernandez, F.; Taladriz, S.; Lopez-Contreras, G.; De La Fuente, B.; Argüelles, J.; Arellano, R. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Firstly, it was studied the relationship between relative force (F rel) of the lower limbs in a isotonic Lunge test, with the performance in a swimming kick start (SS). Afterwards, were applied two Postactivation-Potentiation (PAP) specific warm ups in order to analyze their effect in performance considering the F rel of the subjects. Trained swimmers (n=14) volunteered in this study. Pearson product-moment correlation coefficients were used to verify the relationship between relative force and kinematic variables of a SS. Results revealed high correlation between relative force and performance in SS (Dive Distance: R2=0.872, p<0.001; Horizontal Hip Velocity: R2=0.308, p=0.049; Time to 15m: R2=-0.813, p<0.001). After PAP, swimmers with higher relative force showed a higher improvement on the kinematic variables of SS than those with lower values of strength.